Possibility of using dabigatran in patients with atrial fibrillation and acute coronary syndrome and PCI - A. D. Erlich (Медицинский совет, 2019)
This article is devoted to the problem of combined antithrombotic therapy in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) due to acute coronary syndrome (ACS). Traditionally, these patients require an oral anticoagulant (OAC) to prevent stroke and dual anti-platelet therapy (DAT) to prevent coronary complications. The necessity of combining various antithrombotic drugs, since this greatly increases the risk of bleeding is becoming an increasing relevant clinical problem. The prolonged triple therapy in the form of a combination of OAC and DAT does not bring additional benefit to the patients, but, on the contrary, may be potentially dangerous. Currently, the possibility of using several new oral anticoagulants (NOAC) in patients with AF and ACS/PCI in the form of dual therapy has been proven: combination of OAC and p2Y12 inhibitor. The article focuses on the RE-DUAL PCI study, in which the use of dabigatran at both doses permitted in AF (150 mg twice daily and 110 mg twice daily) in combination with the p2Y12 inhibitor was associated with fewer bleeding complications than during the triple therapy in the form of OAK + DAT.The article presents a clinical case of the possibility of management of a patient with AF and ACS under the modern clinical guidelines, as well as an overview of current guidelines for the use of OAC and DAT in patients with AF undergoing PCI.